Distribution of contagious and environmental mastitis agents isolated from milk samples collected from clinically health buffalo cows between brazilian dry and rainy seasons of the year - Bonini Pardo, R. [UNESP]; Mendoza-Sánchez, G. [UNESP]; Nader Filho, A. [UNESP]; Santos, T. A.B. [UNESP]; Langoni, H. [UNESP]; Tonhati, H. [UNESP]; Ferreira, E. B.S.; Ravena, D. L.; Sturion, D. J.; Maia, R. P. (Taylor & Francis, 2007)
The present study was performed to evaluate the microbiological characteristics of clinically health quarters submitted to milking and also to observe the distribution of contagious and environmental agents between brazilian dry and rainy seasons of the year. During nine months 734 quarters from 37 buffalo cows were submitted monthly to udder inspection, palpation and strip cup test before milking. 734 asseptic milk samples were inoculated in 10% ovine blood agar and in MacConkey agar media, then incubated for 72 hours at 37°C. Among the 580 isolated microrganisms, 182 (31,38%) were recovered from samples collected during the rainy season and 398 (68,62%) from the dry season. In the rainy period the most prevalent agents were: bacteria from the genus Corynebacterium sp (53,30%), Staphylococcus sp (19,78%) and Rhodococcus equi (13,74%). In the dry period, the commonest ones were: Corynebacterium sp (44,97%), Staphylococcus sp (18,84%) and Micrococcus sp (9,55%). The results demonstrated that the methods used to select health quarters in brazilian dairy buffalo farms allow the transmission of contagious bacteria during both seasons of the year, maintaining agents known to cause mainly subclinical inflammatory reactions that compromise cronically the physiology and production of the mammary gland.
Keywords: Buffalo; Mastitis; Microorganisms; Seasons